Auditoría de la identidad e imagen de UPA comunicaciones S.A. - Bone Chevez, Robinson Joao (Machala, 2020)
In the current context of organizations and the dynamics of an increasingly competitive market, intangible assets (reputation, trust, organizational culture, image, etc.) constitute 84% of the total value of the company (Costa, 2018), that is, the differentiating value is not in the idea of the service or product, but in the attributes and organizational characteristics of the brand (Pérez, 2010). In this sense, it is increasingly necessary to analyze the aspects of the company's communication that are contributing to the perceived global image, as an opportunity to identify strengths and weaknesses to act from the strategic vision. Given that everything that happens in the company communicates, being aware of these communication flows will result in a long-term competitive advantage compared to companies that do not evaluate themselves. Organizational communication focuses its interest on designing message flows that favor the performance of relationships and the company as such. The two big mistakes, and the most common ones in business management, are, in the first place, not considering the competition and, from the opposite side, not evaluating oneself. Because of this, the concept of auditing communication and image proposed by Costa (2012) and Cerezo (2013) arises, which, as detailed in the development of the text, is not a new issue; on the contrary, it is one of the ways of analyzing the concept of the company and the components of the image and communication that impregnate it. This vision is contrasted with the contributions of professionals in the area of communication management in the city to execute an effective diagnosis of the case presented in the document. The theoretical references and observations are put into practice in the study of the Upa Comunicaciones S.A. case, a brand with around ten years in the market. A company that has been developing advisory and communication services to entrepreneurs and SMEs (small and medium enterprises) both locally and nationally. Therefore, this research sought to determine the status of the image of the branding agency Upa Comunicaciones S.A. from a mixed approach (qualitative and quantitative), with a theoretical review on communication, image, brand, and auditing, among other concepts, that frame the researcher in the communication-company system. For this diagnosis, we proceeded with the application of surveys, interviews and field observation. Two of these (interviews and surveys) are governed by the structure of a technical-methodological framework that guides the researcher to the effective diagnosis of all the variables and development units proposed in the research design. As a result, a series of conclusions are drawn that help to understand the attributes of the Upa brand from its different particularities (identity, communication, and culture), which are influencing the construction and management of the agency's image. In addition to the propositive approach of possible lines of action, as well as the recommendations that suggest lines of research related to the study of brand communication in the local economy.
En el contexto actual de las organizaciones y la dinámica de un mercado cada vez más competitivo, los activos intangibles (reputación, confianza, cultura organizacional, imagen, etc.) constituyen el 84% del valor total de la empresa (Costa, 2018), es decir, el valor diferenciador no está en la idea del servicio o producto, sino en los atributos y características organizacionales de la marca (R. Pérez, 2010). En este sentido se hace cada vez más necesario analizar los aspectos de la comunicación de la empresa que están contribuyendo a la imagen global percibida, como una oportunidad de identificar fortalezas y debilidades para actuar desde la visión estratégica. Dado que todo lo que sucede en la empresa comunica, estar al tanto de estos flujos de comunicación resultará en una ventaja competitiva a largo plazo en comparación con las empresas que no se autoevalúan. La comunicación organizacional centra su interés en el diseño de flujos de de mensajes que favorezcan el rendimiento de las relaciones y la empresa como tal. Los dos grandes errores, y los más comunes en la gestión empresarial es, en primera instancia, no considerar la competencia y, desde el lado opuesto, no autoevaluarse. Ante ello, surge el concepto de auditoría de la comunicación e imagen propuesta por Costa (2012) y Cerezo (2013), que como se detalla en el desarrollo del texto, no es un tema nuevo; por el contrario, es una de las formas de analizar el constructo empresa y los componentes de la imagen y comunicación que la impregnan. Esta visión es contrastada con las aportaciones de profesionales en el área de la dirección de comunicación de la ciudad con la finalidad de ejecutar un diagnóstico efectivo del caso que se presenta en el documento. Los referentes teóricos y las observaciones se llevan a la práctica en el estudio del caso Upa Comunicaciones S.A., una marca con alrededor de diez años en el mercado. Empresa que ha venido desarrollando servicios de asesoría y comunicación a empresarios y Pymes (pequeñas y medianas empresas) tanto a nivel local como nacional. Por ello, la presente investigación buscó determinar el estatus de la imagen de la agencia de branding Upa Comunicaciones S.A desde un enfoque mixto (cualitativo y cuantitativo), con una revisión teórica sobre la comunicación, imagen, marca y auditoría, entre otros conceptos, que enmarcan al investigador en el sistema de comunicación-empresa. Para este diagnóstico se procedió con la aplicación de encuestas, entrevistas y la observación de campo. Dos de ellos (entrevistas y encuestas) están plasmados se rigen a la estructura de un cuadro técnico metodológico que guía al investigador al diagnóstico efectivo de todas las variables y unidades de desarrollo planteadas en el diseño de investigación. Como resultado, se plantea una serie de conclusiones que ayudan a comprender los atributos de la marca Upa desde sus diferentes particularidades (identidad, comunicación y cultura), mismas que están influyendo en la construcción y gestión de la imagen de la agencia. Además del planteamiento propositivo de posibles líneas de acción, así como las recomendaciones que sugieren líneas de investigación relacionadas al estudio de la comunicación de marcas en la economía local.
Keywords: AUDITORIA DE COMUNICACION; IMAGEN CORPORATIVA; EMPRESA